Oncological Outcomes of Patients With Different Pathological Features of pT3a Renal Tumor: A Systematic Review and Quantitative Synthesis - Guo, Pengju; Wang, Yongxing; Han, Yili; Wei, Dechao; Zhao, Jiahui; Li, Mingchuan; Jiang, Yongguang; Luo, Yong (Frontiers in Oncology, 2021)
Purpose To identify the differences in oncological outcomes for patients with different pT3a renal tumor invasion patterns and pathological features. Methods The protocol of this study was registered on PROSPERO (CRD42021234475). Relevant studies were identified by searching the PubMed, Cochrane library, Embase, and Web of Science databases. Cancer-specific survival (CSS) was selected as the endpoint. Pooled hazard ratio (HR) and 95% confidence interval (CI) extracted from multivariate Cox models were evaluated to identify the hazard association. Results A total of 22 studies, which enrolled 12384 patients were included for quantitative synthesis. Sinus fat invasion (SFI) + perinephric fat invasion (PFI) was associated with inferior CSS compared to SFI only (p = 0.02). Comparable CSS was observed between SFI and PFI (p = 0.57). SFI ± PFI showed inferior CSS compared to PFI only (p = 0.0002). The presence of pelvicalyceal system invasion significantly increased the risk of cancer-specific mortality (p = 0.0005). Renal vein invasion (RVI) indicated poor oncological outcomes in terms of CSS (p = 0.002). The concomitant RVI and fat invasion (FI) significantly increased the risk of deterioration of CSS compared to RVI or FI (p < 0.0001). Multiple invasion patterns translated into a significantly decreased CSS (p < 0.0001). Aggressive tumor behavior, including lymph node involvement (p = 0.006), distant metastases (p < 0.00001), sarcomatoid differentiation (p < 0.0001), necrosis (p < 0.0001), Fuhrman grade III or IV (p < 0.0001), positive margin (p < 0.0001), and tumor size >7cm (p < 0.0001) were the predictors of inferior CSS. The lymphovascular invasion (p = 0.67) was indolent in terms of CSS. Conclusion This study confirmed the heterogenicity of pT3a renal tumors. Multiple invasion patterns could translate into a significantly decreased CSS, and SFI should not be merged in the SFI + PFI group. The presence of PSI or RVI could significantly increase the risk of cancer-specific mortality. Lymph node involvement, distant metastases, sarcomatoid differentiation, necrosis, high Fuhrman grade, positive margin, and size >7cm were the predictors of inferior CSS. A precise-risk grade of CSS for different invasion patterns including comprehensive combinations may be useful for the further refinements of the TNM system. Systematic Review Registration The current study was registered on PROSPERO, and the registration numbers is CRD42021234475.